1987
DOI: 10.1148/radiology.164.1.3108955
|View full text |Cite
|
Sign up to set email alerts
|

Suprasellar germinoma: radiation therapy.

Abstract: From 1974 to 1984, nine patients with suprasellar germinoma were treated with megavoltage radiation therapy. The entire craniospinal axis was irradiated in all patients, with median doses of 45.6 Gy, 31.6 Gy, and 25.2 Gy delivered to the tumor volume, whole brain, and spinal cord, respectively. Two patients have died (14, 11.5 months) without evidence of tumor: one of uncontrolled endocrine dysfunction due to patient noncompliance, the other of hyperosmolar coma. There have been no tumor recurrences with a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…There is no agreement on the optimal radiation dose for the whole brain, but most investigators have applied doses of 25-30 Gy to eradicate microscopic disease. 8,[37][38][39] Shibamoto recommended a low-dose craniospinal irradiation (20 -24 Gy) for patients with positive or negative CSF cytology. 9 There have been no recent reports showing that treatment outcome after high-dose radiation at doses of Ͼ 30 Gy for the whole brain is superior to that of low-dose radiation at Ͻ 30 Gy, and thus it has been suggested that low-dose radiation at Ͻ 30 Gy should be used for the whole brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no agreement on the optimal radiation dose for the whole brain, but most investigators have applied doses of 25-30 Gy to eradicate microscopic disease. 8,[37][38][39] Shibamoto recommended a low-dose craniospinal irradiation (20 -24 Gy) for patients with positive or negative CSF cytology. 9 There have been no recent reports showing that treatment outcome after high-dose radiation at doses of Ͼ 30 Gy for the whole brain is superior to that of low-dose radiation at Ͻ 30 Gy, and thus it has been suggested that low-dose radiation at Ͻ 30 Gy should be used for the whole brain.…”
Section: Discussionmentioning
confidence: 99%
“…9 There have been no recent reports showing that treatment outcome after high-dose radiation at doses of Ͼ 30 Gy for the whole brain is superior to that of low-dose radiation at Ͻ 30 Gy, and thus it has been suggested that low-dose radiation at Ͻ 30 Gy should be used for the whole brain. 8,[37][38][39] New treatment strategies, including chemotherapy alone without radiotherapy or combined local irradiation with systemic chemotherapy, have been performed to avoid radiation-induced brain damage. 16,17,22,40,41 Allen conducted a Phase II study that was designed to selectively reduce the radiation dose in patients showing a complete response to neoadjuvant carboplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors report favourable results following CSI in children who present with CNS GCT beyond puberty where late morbidity would be acceptable [6,9,16,21,[27][28][29]. Most favour low dose CSI [13,16,22,23,[30][31][32].…”
Section: Cranio-spinal Irradiation (Csi)mentioning
confidence: 99%
“…When compared to smaller radiation therapy fields, WBRT was shown to provide better results in one centre where CT scan and MRI were not routinely available [37]. Others have also reported more favourable results following WBRT [24,28,37,47]. Some have quoted intracranial recurrence rates of up to 15% when full cranial irradiation was not utilised [24,48,49].…”
Section: Local Field Irradiationmentioning
confidence: 99%
“…Doses of primary site irradiation in most series have ranged between 4,000 and 5,500 cGy [32][33][34][35][36][37][38][39][40][41]. Some studies have suggested poorer survival if doses lower than 4,000 cGy of radiation are delivered to the primary site [1,40] (Table 3).…”
Section: Management: Germinomasmentioning
confidence: 99%